Tinjauan Kuat Lentur Balok Beton Bertulang Dengan Tambahan Tulangan Baja Menyilang Pasca Bakar Dengan Berbagai Variasi Waktu - ABDUL AZIZ, MUHAMMAD, Basuki, S.T, M.T, Yenny Nurchasanah, S.T, M,T (2015)
Heating in concrete due to fire would result in a fundamental change of its nature. The concrete will be cracked, spalled, and loss of its strenght. Loss of strenght occurs because the chemical composition changes gradually in the cement paste. A fire would caused a fears of the collapse of a building, because the construction of the building is not safe anymore. Therefore the reinforcement of concrete beams need to be reinforced with additional steel bars are fitted crosswise to add the strenght flexure of its and reduce the risk of crack increment. This research is aims to determine the flexure strenght of reinforced beams with the addition of steels are fitted crosswise before and after burned and to compare the flexure srtenght of reinforced concrete beams are testing in laboratory experiments and analytically. Materials used in this study are sand, cement, gravel, water, and steel reinforcement. The conctrete plans based on a comparison of the cement, sand, and gravel is 1:2:3 that produce f'c = 16,26 Mpa. The factor of cement water (f.a.s) used is 0,5. In this research, variations of burning time is 0, 30, 60, 90, and 120 minute. The result showed that moment capacity of concrete beams without burning is 15,532 kN.m, moment capacity of concrete beams after burned for 30 minute is 14,531 kN.m, moment capacity of concrete beams after burned for 60 minute is 12,495 kN.m, moment capacity of concrete beams after burned for 90 minute is 8,859 kN.m, moment capacity of concrete beams after burned for 120 minute is 7,207 kN.m. Analitically, the result of moment capacity of concrete beams without burning is 14,876 kN.m, moment capacity of concrete beams after burned for 30 minute is 14,534 kN.m, moment capacity of concrete beams after burned for 60 minute is 13,975 kN.m, moment capacity of concrete beams after burned for 90 minute is 13,794 kN.m, and moment capacity of concrete beams after burned for 120 minute is 13,424 kN.m. the result also showed that there is always a decline in the flexure strenght of reinforced beams with increasing time of fuel. Key word : Reinforced concrete beams, Post-combustion, moment capacityof beam